Coronavirus and Pregnancy: The Challenges of the 21st Century: A Review - Adam, Sumaiya; Pheiffer, Carmen; Dias, Stephanie; Hlongwane, Tsakane; Vannevel, Valerie; Soma-Pillay, Priya; Abdullah, Fareed (Frontiers in Microbiology, 2022)
Despite many advances in medicine we are still faced with emerging pathogens. Pregnant women have been disproportionately affected by previous coronavirus outbreaks. The COVID-19 pandemic has not affected pregnant women as greatly as SARS-CoV and MERS, but has posed other challenges such as the need for quarantine and isolation, limited access to antenatal care, use of personal protective equipment, and vaccine hesitancy. This review will describe the impact of the significant coronaviruses on pregnancy, with special focus on the challenges being encountered by the SARS-CoV-2 global pandemic.